Suscetibilidade a antimicrobianos e genes de virulência em Salmonella enterica de origem avícola - Oliveira, Aline Pedrosa de (2016)
Salmonella enterica is a foodborne pathogen with multifactorial and complex pathogenic mechanisms. Identification of the presence of virulence genes and antimicrobial resistance profiles in isolates of poultry origin provides relevant information on the risk attributed to the consumption of products contaminated by the agent. The objective of this study was to verify the susceptibility profile of Salmonella enterica for nalidixic acid (30μg), amicacin (30μg), ampicillin (10mg), ceftiofur (30μg), chloramphenicol (30μg), ciprofloxacin (5μg), enrofloxacin (5μg), streptomycin (10mg), gentamicin (10mg), tetracycline (30μg), tobramycin (10mg) and trimethoprim (5μg) used in both human and animal medicine, to investigate the presence of multiresistant isolates, to detect the presence of the variable region of the class 1 Integron, to analyze the association between the presence of Class 1 Integron and antimicrobial resistance and to evaluate the presence of virulence genes located in the islands of virulence 1 (invA) and 2 (sseD), gene encoding long polar fimbriae (lpfA) and plasmidial spvR, to identify the virulence profiles and pathogenicity potential of Salmonella enterica serovars isolated from carcasses, hearts, livers, gizzards and environment of slaughterhouses located in the State of Goiás and on chicken carcasses marketed in commercial establishments in Goiânia -GO. The highest resistance frequency was observed for ceftiofur, 19.12% (13/68), followed by streptomycin, gentamicin, tobramycin, tetracycline and trimetropic, 16.18% (11/68) both, nalidixic acid 14.71% (10/68), ampicillin 13.24% (9/68), and enrofloxacin 2,94% (2/68). No resistance was observed for ciprofloxacin, only intermediate, 45.59% (31/68), 100% (68/68) of the isolates were sensitive to amikacin and chloramphenicol. Of the 68 isolates 22 (32.35%) were resistant to one or more antimicrobial principles. Twelve profiles of antimicrobial resistance were identified, 54.54% (12/22) of the isolates presented multiresistance. The variable region of Class 1 Integron was detected in 63.23% (43/68) of the isolates. The presence of this region was not associated with antimicrobial resistance. All slaughterhouses and in most commercial establishments it was possible to identify Salmonella enterica carrying the Integron of class 1 demonstrating the ubiquity of the same. The invA gene was identified in 100% (59/59), sseD in 92.53% (54/59), lpfA in 86.51% (52/54) and spvR in 86.18% (49/59) of the serovars of Salmonella enterica. Six virulence profiles were identified, 77.97% of the isolates were grouped in profile A characterized by the presence of the four virulence genes simultaneously. The knowledge of the virulence profiles of the isolates allows to affirm that the serovars identified in the state of Goiás are potentially virulent and capable of triggering disease in poultry production systems and in humans.